The Impact of Ambient Air Pollution on Hospital Admissions - Massimo Filippini; Giuliano Masiero; Sandro Steinbach (ETH Zurich, CER-ETH - Center of Economic Research, 2017)
Ambient air pollution is the environmental factor with the greatest impact on human health. Several epidemiological studies provide evidence for an association between ambient air pollution and human health. However, the recent economic literature has challenged the identification strategy used in these studies. This paper contributes to the ongoing discussion by investigating the association between ambient air pollution and morbidity using hospital admission data from Switzerland. Our identification strategy rests on the construction of geographically explicit pollution measures derived from a dispersion model that replicates atmospheric conditions and accounts for several emission sources. The reduced form estimates account for location and time fixed effects and show that ambient air pollution is strongly correlated with hospital admissions. In particular, we find that SO2 and NO2 are positively associated with admission rates for coronary artery and cerebrovascular diseases. As a robustness check, we adopt instrumental variable methods to account for the possible endogeneity of pollution measures. These results may contribute to a more accurate evaluation of future environmental policies aiming at a reduction of ambient air pollution exposure.
Keywords: I10; Q51; Q53; 330; Ambient air pollution; dispersion model; hospital admissions; count panel data